Clinical profiles and treatment outcomes of dental rehabilitation in patients treated under general anesthesia: a comparison between healthy and special healthcare needs children - Al-Khotani, Amal; Ajabnoor, Hossam; Koshak, Renad; Alshehri, Shahad A.; Meisha, Dalia E. (Frontiers in Pediatrics, 2025)
BackgroundThe dental treatment of pediatric patients under general anesthesia is considered one of the most important behavioral management techniques that parents have accepted. The aim of this study is to compare the clinical profiles and treatment outcomes of healthy patients and special healthcare needs (SHCN) pediatric dental patients who underwent a full dental rehabilitation under general anesthesia (DRGA).MethodsThis study utilizes a retrospective cross-sectional design. Records were reviewed for all pediatric patients referred to the dental clinic from December 2020 to June 2023 and placed on the waiting list for DRGA. The data collected included demographics, medical history, types of dental treatment performed, medications prescribed, and admission/discharge details. Statistical analyses included chi-square, Fisher's exact, Mann–Whitney U, Kruskal–Wallis tests, as appropriate, and logistic regression.ResultsThis study involved 378 pediatric dental patients treated under general anesthesia (GA), 46.3% were classified as healthy, while 53.7% had SHCN. The SHCN group was significantly older (mean age 6.6 ± 2.7 years vs. 5.1 ± 1.6 years, p < 0.0001) and required more extensive treatments, including extractions (p < 0.0001), longer hospital stays (mean: 5.9 vs. 0.9 days, p < 0.0001), and more frequent preoperative consultations (p < 0.0001). The group with children younger than 6 years had a higher proportion of healthy patients (73.9%), received more conservative treatment such as stainless-steel crowns and pulpotomies (p < 0.0001), and had shorter hospital stays by 1.3 days compared to the 6–14-year-old group. SHCN status was a strong predictor of admission after DRGA compared to healthy ones (OR: 59).ConclusionThis study highlights the distinct differences in the clinical profiles and treatment outcomes of healthy patients and SHCN pediatric patients undergoing DRGA, with the latter patients requiring more complex care and experiencing extended hospitalization. These findings underscore the importance of tailoring dental treatment plans to the unique needs of pediatric patients to optimize outcomes.